2017
DOI: 10.1007/s00432-017-2396-4
|View full text |Cite
|
Sign up to set email alerts
|

Lung carcinoma progression and survival versus amino- and carboxyl-parathyroid hormone-related protein expression

Abstract: Amino PTHrP and carboxyl PTHrP can vary independently in different lung carcinomas. Carboxyl PTHrP may temper the stimulatory effect of amino PTHrP on cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the past years, several authors have reported a correlation between the overexpression of PTHrP and tumor progression in lung, breast, and prostate cancers[ 16 , 21 , 60 ]. Our research group has shown that this cytokine also promotes the aggressive phenotype of intestinal tumor cells[ 13 , 24 - 26 ] .…”
Section: Resultsmentioning
confidence: 99%
“…In the past years, several authors have reported a correlation between the overexpression of PTHrP and tumor progression in lung, breast, and prostate cancers[ 16 , 21 , 60 ]. Our research group has shown that this cytokine also promotes the aggressive phenotype of intestinal tumor cells[ 13 , 24 - 26 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Elevated serum levels of PTHrP were correlated with an increased frequency of bone metastases and shorter survival in lung carcinoma patients with hypercalcemia ( n = 23) 35 . Interestingly, carboxyl terminal PTHrP peptide was described as a positive prognostic indicator for survival in female patients with NSCLC while amino terminal PTHrP peptide, which can stimulate thermogenic gene expression and induce cachexia, was found to be a negative survival factor in lung adenocarcinoma 13,36 . While negative influence of high PTHLH mRNA on overall survival of the patients may depend on potential oncogenic effects driven by PTHrP protein, 37 it is possible that PTHrP‐associated cancer cachexia may contribute to the worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Interestingly, carboxyl terminal PTHrP peptide was described as a positive prognostic indicator for survival in female patients with NSCLC while amino terminal PTHrP peptide, which can stimulate thermogenic gene expression and induce cachexia, was found to be a negative survival factor in lung adenocarcinoma. 13 , 36 While negative influence of high PTHLH mRNA on overall survival of the patients may depend on potential oncogenic effects driven by PTHrP protein, 37 it is possible that PTHrP‐associated cancer cachexia may contribute to the worse outcome. Our findings argue that EGFR signalling regulates PTHrP expression in tumours, thus the cachectic effects of PTHrP may be pronounced in patients with EGFR active tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is noteworthy that different tissues or malignancies have specific and different post-translational processing, producing different proportions of daughter peptides from the three PTHrP isoforms, leading to prevalent paracrine, autocrine, or intracrine effects [ 6 , 49 ]. In fact, in lung carcinoma, the expression of amino and carboxyl regions of PTHrP can vary independently in different tumor cases, so that the presence of amino PTHrP and PTH1R worsen the prognosis in lung cancer patients [ 32 ], while, carboxyl PTHrP, when present, may lower the stimulatory effect of amino PTHrP [ 50 ]. Moreover, many evidences indicate that discrete PTHrP fragments exert multiple effects on different neoplastic cell populations via cytosolic and nuclear targets, by functioning in different settings either as inducers of cell proliferation or leading to cell death and apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%